THE VOLTAGE STABILITY ANALYSIS OF SHIP ELECTRICAL POWER SYSTEM USING ARTIFICIAL NEURAL NETWORK(ANN) - Pramod. N. Manure; Vishwajit Bhosale; Prof. B. Sampath Kumar (International Journal of Innovations in Engineering Research and Technology, 2022)
An crucial, independent electric power system for ships is the ship’s electric power system. Increased ship tonnage and a rise in the number of electric-powered ships result in an increase in the generator capacity at a marine power plant. Modern marines use electric propulsion technology, so the voltage stability control system needs to be more effective. The electricity generated by diesel generators drives a vessel’s propulsion system in addition to being sent to each load. If the marine power system’s voltage is not maintained within an acceptable range, the marine electrical system will be severely harmed. The idea of voltage stability and the current state of the research were first summarised in this work. A critical step in a voltage stability analysis is choosing the right load model because any factor that significantly raises tension losses also raises load losses. A critical step in a voltage stability analysis is choosing the right load model because any factor that significantly raises tension losses also raises load losses. The load model construction issue for the ship power system has been investigated. Then, a brand-new index that is simple to calculate and can be used for online usage was introduced to address the voltage stability index issue. The lack of complex matrix calculations or other time-consuming calculations should result in faster results with this strategy. In order to assess voltage stability and certify secure and unsecure power system modes, this study uses artificial neural networks (ANNs). supplying the neural network with data In the MATLAB simulation environment, the network is subject to transmission line settings, sensors, feedback, and point load flow analysis.